Energy efficiency measures on two different commercial buildings in Malaysia - Nor Azuana Ramli; Mohd Fairuz Abd Hamid; Harison Gimang Richard (Penerbit Universiti Kebangsaan Malaysia, 2019)
Buildings consume almost the highest energy in Malaysia, and the highest energy consumption comes from electricity. In order to reduce energy consumption in the commercial buildings, energy efficiency measures need to be done based on factors that affect energy consumption in the building. In this paper, the energy consumption of two commercial buildings are taken as a case study, and a number of energy cost saving measures were proposed based on the energy audit. The primary objective of this study is to obtain the minimum years of return of investment for two different commercial buildings through energy efficiency measures. In this case study, energy prediction is added and its results are used to determine how much saving could be obtained. The methodology used for prediction of energy consumption is autoregressive integrated moving average, and its performance was compared with linear regression and artificial neural network. The results showed that the most accurate method with the highest cost saving is autoregressive integrated moving average. Finally, building energy index was calculated, and the results showed that the minimum years of return on investment is two years if the investment is RM 499,539. For future work, other factors such as the number of equipment should be included in the prediction analysis to obtain more accurate results.